Pattern Visual Evoked Potential (VEP) is unaffected in the early stage of mild cognitive impairment - Lau, Chean Ling; Norhani Mohidin,; Azzatul Ainur Mohd Kamal,; Zainora Mohammed,; Bariah Mohd Ali, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The aim of this study was to determine whether pattern-reversal Visual Evoked Potential (PRVEP) is affected in mild cognitive impairment (MCI). Participants aged ≥ 60 years diagnosed as MCI were invited to participate in a study together with a group of controls. PRVEP was measured using A RETI-port/Scan 21 and stimuli of large and small checks sizes, 1° (60 min of arc) and 0.25° (15 min) respectively were used to obtain responses. The amplitude and implicit times of the MCI and control groups were then compared. A total of 18 MCI participants (age 65.7 ± 3.1 years) and 18 controls (65.1 ± 3.8 years) consented to participate in the study. The amplitude and implicit times for the MCI group using the target sizes of 60 min of arc were 9.80 ± 4.06 μV and 108.83 ± 7.63 ms and for 30 min of arc were 11.00 ± 7.44 μV and 123.96 ± 6.18 ms respectively. Consecutively for the control groups the amplitudes and implicit times were 8.96 ± 3.52μV, 105.85 ± 3.60 ms and 11.97± 6.11 μV, 122.57 ± 8.28 ms. PRVEP results did not reveal significant differences in P100-wave amplitude nor implicit time between the two groups under investigation. This study concluded that the visual pathway of MCI participants may be unaffected in the early part of the disease process.